Pengaruh Lama Pemasakan terhadap Kadar Protein, Lemak, Profil Asam Amino, dan Asam Lemak Tepung Ikan Sepat Rawa (Trichogaster trichopterus): Effect of Different Cooking Time on Protein and Fat Content, Amino Acid and Fatty Acid Profile of Three Spot Gourami (Trichogaster trichopterus) Fish Flour - Rabiatul Adawyah; Siti Khusnul Khotiffah; Wahyudinur; Findya Puspitasari (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2020)
Three spot gourami (Trichogaster trichopterus) population in South Kalimantan is abundant but not yet utilized optimally. Processing three spot gourami into fish flour is expected to maximize its utilization. This study aimed to understand the effect of different cooking time in three spot gourami fish flour processing on protein and fat content, amino acid, and fatty acid profile. The design of this study was experimental with a completely randomized design method. The protein content was analyzed by kjeldahl method, amino acid analyzed by High Performance Liquid Chromatography (HPLC) method, lipid content analyzed by the soxhlet method and fatty acid analyzed by Gas Chromatography (GC). The treatments used were cooking using a pan for 30 minutes (A), autoclave 20 minutes (B), and autoclave 30 minutes (C). The results showed the treatment affected protein and fat content, as well as amino acid and fatty acid profiles. The highest protein content in treatment C 63.76%, the lowest fat content in treatment B 3.53%. For the amino acid profile, lysine is the highest type of essential amino acid, while the highest type of nonessential amino acid is glutamic acid, and in the fatty acid profile there are 23 types of fatty acids, the highest is palmitic acid with an average 21.66%, followed by oleic acid d 17.49% and linoleic acid 6.69%.